Ectoparasites and haemoparasites of indigenous chicken (gallus domesticus) in Ibadan and environs. (2003)
This research undertook the study of ectoparasites and haemoparasites found on and in the body of indigenous chicken (Gallus domesticus). Six hundred and nineteen ectoparasites were collected from 375 chicken from 28 households in and around Ibadan city between February and November, 1999. Of these, 455 (72.72%) were lice, among which 253 (40.12%) were Menopon ga/linae, 53 (8.4%) were Columbicola columbae, 48 (7.75%) were Goniocotes hologuster, 33 (5.33%) were Goniodes gigas, 31 (5%) were Chelopistes meleagridis, 23 (3.7%) were Liperus capon is and 15 (2.42%) were Cuclotogaster heterographus. One hundred and twenty one (19.55%) were identified as the soft tick Argas persicus. Fourty three (6.94%) mites, identified as Dermanyssus gallinae were also found. Giemsa stained smears from 150 uncoagulated chicken blood samples examined at x 1,000 magnification, revealed presence of Plasmodium species (spp.) in 48 (32%) of the samples. Leucocytozoon spp accounted for 30 (20%), while Haemoproteus spp was identified in two (1.3%) of the samples. Mixed infection with Plasmodium spp and Leucocytozoon spp w'ere identified in 14 (9.33%), while Leucocytozoon spp and Plaemoproteus spp were identified in four (2.67%) of the blood samples. Six (4%) of the blood samples have the three haemoparasites. The need to control these ectoparasites was stressed